A Survey on Techniques Adopted in the Prioritization of Test Cases for Regression Testing - Bruce. E, John; Sasi Prabha, T (International Journal of Engineering and Technology, 2018)
Â Regression testing is testing the software with the intention to confirm that changes made on part of a module do not necessitate other parts of the module. Test case prioritization helps to reduce regression testing cost by ordering the test cases in such a way that it produces optimized results. Code Coverage and Fault detection being the factors behind the prioritization is dealt with techniques like Heuristic method, Meta Heuristic methods and Data mining techniques. The effectiveness of the techniques applied can be evaluated with the metrics like Average Percentage of Fault Detection (APFD) , Average Percentage Block Coverage (APBC), Average Percentage Decision Coverage (APDC) etc . In this paper,, a detailed survey on the various techniques adopted for the prioritization of test cases are presented.Â
Keywords: Code Coverage; Greedy; Machine Learning; Meta Heuristic; Prioritization; etc.